The Implementation of Paikem Gembrot Strategy in Arabic Learning Based on 21st Century - Shidik Alfatha; Nofrizal Nofrizal; Fitri Aisyah (Institut Agama Islam Negeri Imam Bonjol Padang, 2024)
This study aims to show how the strategies of teachers and all related elements in increasing students' motivation and understanding of Arabic in the digital era. This study examines the efficacy of this strategy in improving Arabic comprehension by adapting it to the digital era, also integrating digital technology by learning applications. The method used in this research is field research with a descriptive qualitative approach. Data was collected by conducting observations, interviews, and documentations. The results of this study indicate that the PAIKEM GEMBROT strategy applied in Arabic language learning is realized in five actions, namely: 1) pre-learning vocabulary submition, 2) utilization of pocket dictionary, 3) using motivational strategies, 4) Building bi’ah ‘Arabiyah at school, and 5) optimizing the use of technology. The implementation of PAIKEM GEMBROT strategy in Arabic learning at the school is considered successful in increasing students' enthusiasm for learning, and student learning outcomes have increased over the past 2 years. Technology integration makes it easier for students to understand the material, more involved in learning, and can develop modern skills. Based on the findings of this study, it is recommended that future Arabic language learning at madrasahs integrates the PAIKEM GEMBROT strategy with 21st-century educational technology. Teachers should enhance their digital literacy and utilize interactive media such as mobile learning apps and online quizzes to foster active and joyful learning environments. Additionally, the development of learning modules and worksheets should incorporate 4C skills (critical thinking, creativity, collaboration, and communication). Project-Based Learning (PjBL) is also suggested to enable students to apply Arabic in real-life contexts. Authentic assessments using digital platforms should be implemented to evaluate student performance more comprehensively. Further research is encouraged across different madrasah contexts, and collaboration between Arabic and ICT teachers is essential to create innovative, technology-enhanced Arabic learning experiences.